A case study on the stability of the shield excavation face in full-section coarse sand. (May 2019) - Cheng, Cheng; Zhao, Wen; Qi, Diyang; Han, Jianyong; Jia, Pengjiao; Chen, Yang; Bai, Qian
Highlights: The process of earth chamber pressure monitoring in project of the Xi'an Metro Line 4 was introduced. Detailed variation of the earth chamber pressure in coarse sand stratum were shown and analyzed. The feasibility of silo-wedge model in practical application was studied. The groundwater significantly weakens the necessary face support pressure to balance the lateral earth pressure of the excavation face. The applicability of theoretical hypothesis of various silo-wedge models were analyzed. Abstract: The estimation of the shield face support pressure is essential for the stability of the shield excavation face. The face support pressure of the earth pressure balance (EPB) shield tunneling machine is mainly composed of the support pressure of the cutterhead and the earth chamber pressure. To ensure the requirements of safe construction, the theoretical face support pressure is one of the most significant references for the earth chamber pressure setting. This paper analyzed the in situ monitoring data of the shield earth chamber pressure from a shield tunneling project of the Xi'an Metro Line 4 in full-section coarse sand. A nonlinear stepwise increase in the earth chamber pressure from the top to the bottom of the tunnel face was obtained. The fluctuation range of the earth chamber pressure gradually increased with an increase in the cover depth. Meanwhile, several types of silo-wedge models were established according to different assumptions proposed by previous studies and this paper. The rationality of their calculations and the applicability of related assumptions were discussed based on practical engineering and new working conditions.